FTA develops a predictive breeding tool to save the Shea Tree in Africa intended to benefit women and smallholder farmers - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA experts explore new means to bring back the declining shea populations on farmlands and parklands by providing improved planting material bred using genomics, a solution that could save the tree that also provides millions of households with a highly nutritious cooking oil, as well as a vital source of income, with its supply chain almost entirely controlled by women.